Emission, kinetic and magnetic phenomena in rare-earth and transition metal doped ZnSe single crystals - Radevici, Ivan (fi=Turun yliopisto|en=University of Turku|, 2015)
In this work emission, optical, electrical and magnetic properties of the d- and f- elements doped zinc selenide crystals were investigated within a wide temperature range. Doping was performed in various technological processes: during the growth by chemical vapor transport method; by thermal diffusion from the Bi or Zn melt. Concentration of the doping impurity in the crystals was controlled by amount of the dopant in the source material or by its concentration in the doping media. Special interest in the work was paid to the influence of the different concentrations of Cr and Yb impurities on ZnSe crystals’ properties, correlations between observed effects and similarities with the Ni, Mn and Gd dopants are analysed. Possibility of formation of the excitons bound to the doping d-ions was shown. In contrast to this, it was observed that f-elements do not bound excitons, but prevent formation of excitons bound to some uncontrolled impurities. A mechanism of Cr doping impurity interaction with background impurities and zinc selenide structural defects was proposed based on experimental data. An assumption about resonant energy transfer between double charged chromium ions and complexes based on crystals’ vacancy defects was made. A correlation between emission and magnetic properties of the d- ions doped samples was established. Based on this correlation a mechanism explaining the concentration quench of the emission was proposed. It was found that f-ions bind electrically active shallow and deep donor and acceptor states of background impurity to electrically neutral complexes. This may be observed as “purification” of ZnSe crystals by doping with the rare-earth elements, resulting i tendency of the properties of f-ion doped crystals to the properties of intrinsic crystals, but with smaller concentration of uncontrolled native and impurity defects. A possible interpretation of this effect was proposed. It was shown that selenium substituting impurities decrease efficiency of the Yb doping. Based on this experimental results an attempt to determine ytterbium ion surroundings in the crystal lattice was made. It was shown that co-doping of zinc selenide crystals with the d- and f- ions leads to the combination of the impurities influence on the material’s properties. On the basis of obtained data an interaction mechanism of the d- and f-elements co-dopants was proposed. Guided by the model of the ytterbium ion incorporation in the selenide sublattice of the ZnSe crystals, an assumption about stabilization of single charged chromium ions in the zinc sublattice crystal nodes, by means of formation of the local charge compensating clusters, was made.

Tässä työssä tutkittiin d- ja f-alkuaineilla doopattujen ZnSe-kiteiden emissio-, optisia,sähköisiä ja magneettisia ominaisuuksia laajalla lämpötila-alueella. Dooppaus tehtiin eri tekniikoilla: kasvatuksen aikana kemiallisesessa kaasufaasikasvatuksessa ja termisellä diffuusiolla Bi- tai Zn-nesteestä. Dooppauksen määrä kontrolloitiin säätämällä dopantin määrää lähtöaineissa tai sen konsentraatiolla dooppausnesteessä. Erityisesti tutkittiin Cr- ja Yb-atomien konsentraation vaikutusta ZnSe-kiteiden ominaisuuksiin sekä korrelaatioita havaittujen ilmiöiden välillä ja yhtäläisyyksiä Ni-, Mn- ja Gd-ioneilla doopattuihin kiteisiin. Työssä osoitettiin, että d-ionien sitomien eksitonien syntyminen on mahdollista. Sen sijaan f-ionit eivät sido eksitoneja, vaan estävät niiden synnyn kontrolloimattomien epäpuhtausionien ympäristöön. Pohjautuen kokeelliseen dataan ehdotettiin, että resonoiva energian siirto Cr2+-ionien ja kiteessä olevien vakanssien välillä selittää Cr-dopantin vuorovaikutuksen kontrolloimattomien epäpuhtausatomien kanssa. Työssä havaittiin myös korrelaatio magneettisten ja emissio-ominaisuuksien välillä d-atomeilla doopatuissa näytteissä ja tähän perustuen ehdotettiin mekanismia, joka selittää emission häviämisen dopantin konsentraation kasvaessa. f-ionien havaittiin sitoutuvan kontrolloimattomien epäipuhtausatomien muodostamiin sähköisesti aktiivisiin mataliin ja syviin donori- ja akseptoritiloihin ja yhdessä ne muodostavat sähköisesti neutraaleja komplekseja. Tämän havaittiin näyttävän kiteen “puhdistumisena”, kun sitä doopataan harvinaisilla maametalleilla: kiteen ominaisuudet ovat yhä lähempänä täysin puhtaan ZnSe:n ominaisuuksia. Tälle ilmiölle esitettiin syntymekanismi. Työssä osoitettiin myös, että seleenin korvaavat epäpuhtaudet vähentävät Yb-dooppauksen tehoa. Tähän perustuen yritettiin määrittää Yb-ionien ympäristöä kidehilassa. Työssä osoitettiin myös, että ZnSe-kiteiden dooppaaminen samanaikaisesti d- ja f-atomeilla johtaa dopanttien yhteisvaikutukseen kiteiden ominaisuuksissa. Kokeiden tuloksena ehdotettiin vuorovaikutusmekanismia dopanttien välille, jossa Yb-ionit korvaavat Se-ioneita Se-alihilassa ja samalla stabiloivat Cr+-ioneita Zn-alihilassa muodostamalla paikallisia varauksen kompensoivia klustereita.